Where does infiltrated stormwater go? Interactions with vegetation and subsurface anthropogenic features - Bonneau, Jeremie; Fletcher, Tim D.; Costelloe, Justin F.; Poelsma, Peter J.; James, Robert B.; Burns, Matthew J. (Journal of hydrology (Amsterdam), 2018)
•Groundwater levels were significantly raised downslope of an infiltration basin.•A large part of the plume of infiltrated stormwater was lost to evapotranspiration.•No infiltrated stormwater contributed to baseflow in the expected stream reach in summer.•In winter, infiltrated water contributed to raised near-stream groundwater levels. The practice of stormwater infiltration is widely used to reduce the amount of urban stormwater runoff delivered to drainage systems and receiving waters. In theory, the practice recharges groundwater, leading to increased urban stream baseflow. In reality, however, little is known about the fate of infiltrated stormwater. Because urban groundwater pathways are numerous and the interactions with subsurface infrastructure (e.g. trenches, pipes, etc.) are highly complex, the spatial and temporal variability of the contribution of infiltrated stormwater to baseflow is difficult to predict. We tracked the fate of infiltrated stormwater out of an 1800 m2 infiltration basin (3.5% of its 5-ha impervious catchment) using a network of piezometers for over three years. We found that groundwater levels downslope of the basin were increased (up to 4 m) while water levels in an array of reference piezometers lateral to the basin showed no change (dry at depths ranging 2–4 m). Monthly water balance calculations indicated that in summer, most of the infiltrated stormwater was evapotranspired by the vegetation downslope of the basin, and thus did not reach the receiving stream. In the colder months, some infiltrated stormwater did reach the stream as plant water use declined. Anthropogenic disturbances (a sewer pipe and stream re-alignment) interacted with the upper part of the plume of infiltrated stormwater, locally lowering the water table. The study provides evidence that the fate of infiltrated stormwater is complex, and that infiltrated stormwater does not always reach receiving streams as baseflow as is often assumed.